The Life Experiences of Loss and Grieving for Indonesian Wives Who Had Lost Their Husbands Because of a Critical Illness: A Case Study - Priambodo AP; Hidayati NO; Nuraeni A (International Medical Case Reports Journal)
Ayu Prawesti Priambodo,1,* Nur Oktavia Hidayati,2,* Aan Nuraeni1,* 1Department of Emergency and Critical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Mental Health Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia*These authors contributed equally to this workCorrespondence: Ayu Prawesti Priambodo, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +62-8112254848, Fax +62-2287793411, Email ayu.prawesti@unpad.ac.idBackground: Grieving is an experience of deep mental suffering. It is a very individual process. Grief over the loss of a spouse can have an impact on both physical and mental health. In the case of an acute or critical event, it will be harder for the spouse to adjust to and accept death, which can lead to mental health problems. Gender is one of the factors that influence the grieving process. There is a more profound understanding of grief in men than in women.Purpose: The study aims to understand widows’ perception, experience, and meaning of loss and grieving.Methods: A case report reviewed the life experiences of loss and grieving of Indonesian wife who had lost their husbands because of a critical illness. Data were collected through in-depth interviews with Individuals. It was conducted using Zoom and recorded. The analysis method uses thematic analysis.Results: Four major themes were described in the case: experiencing the pain of the loss, searching for the meaning of being lost, embracing the new being, and exploring unmet needs in a widow. From this case, it can be concluded that grieving is a complex and dynamic process.Conclusion: In grieving, women express solid and varied emotions and focus on their need to be understood and accompanied. They experience a transition from an experience of anger and emptiness to a sense of finding meaning in their loss and becoming more able to engage with life. The child is an essential factor in the grieving process, as it keeps participants engaged in the world even when faced with the immediate effects of grief.Keywords: critical illness, grieving, life expériences, loss, widow